Intestinal epithelial cell-derived components regulate transcriptome of Lactobacillus rhamnosus GG - Schalich, Kasey; Rajagopala, Seesandra; Das, Suman; O’Connell, Ryan; Yan, Fang (Frontiers in Microbiology, 2023)
Intestinal epithelial cells (IECs) provide the frontline responses to the gut microbiota for maintaining intestinal homeostasis. Our previous work revealed the functional impact of IEC-derived components on Lactobacillus rhamnosus GG (LGG). This study aimed to elucidate the regulatory effects of IEC-derived components on LGG at the molecular level by functional analysis of transcriptome data. The gene expression profiles of LGG treated with IEC-derived components was significantly different from that of control LGG. The Clusters of Orthologous Groups (COGs) and Gene Ontology (GO) analysis demonstrated that the predominant genes enriched by IEC-derived components are involved in amino acid, metal, and sugar transport, biosynthesis of amino acids, fatty acids, and cell wall components, cell division, and translation, while the main repressed genes are associated with the metabolism of amino acids, purines, carbohydrates, glycerophospholipid, and transcription. Further, IEC-derived components promoted LGG growth, which reflects the effects of the increase in transcriptome profile on facilitating nutrient acquisition. These results provide mechanistic insight on the interactions between IECs and the gut microbiota.